Analysis of Differences in Productivity and Income of Maize Farming Using Bisi-2 Seeds and Local Maize in Marobea Village, Sawerigadi District, West Muna Regency - Yumis Rawati; Muhammad Aswar Limi; Agustono Slamet (International Journal of Technology and Education Research, 2025)
This study aims to find out: (1) How the Productivity Level of Corn Farming Using Bisi-2Seeds in Marobea Village, Sawerigadi District, West Muna Regency (2) How the Income of Corn Farming Using Bisi-2 Seeds in Marobea Village, Sawerigadi District, West Muna Regency. The determination of the location of this research was chosen deliberately (purposive). The data collected in this study is by using primary data obtained from the results of direct interviews with farmers using a list of questions/questionnaires and secondary data that have been processed and obtained from agencies related to various sources of literature, journals, books, and the Central Statistics Agency (BPS) or from related parties. The sampling method was carried out using a proportional stratified withdrawal method from each element of the population that was sampled and sampling was carried out randomly (Proportionate Stratified Random Sampling), with a total of 35 farmers. The data analysis used in this study is productivity and income analysis. Results of the study (1) The average productivity of bisi-2 corn in Marobea Village, Sawerigadi District, West Muna Regency is 2,610 kg/ha/planting season. Meanwhile, the average local corn productivity is 991 kg/ha/planting season (2) The average total income of corn farming using bisi-2 seeds in Marobea Village, Sawerigadi District, West Muna Regency is Rp6,503,082/planting season. Meanwhile, the average income of local corn farming obtained was Rp399,333/planting season (3) The productivity and income of bisi-2 corn and local corn farming in Marobea Village, Sawerigadi District, West Muna Regency showed a difference of .000 < 0.05 so that there was a difference between the productivity and income of bisi-2 and local corn.